2017
DOI: 10.1080/08870446.2017.1373113
|View full text |Cite
|
Sign up to set email alerts
|

An illness-specific version of the Revised Illness Perception Questionnaire in patients with atrial fibrillation (AF IPQ-R): Unpacking beliefs about treatment control, personal control and symptom triggers

Abstract: Objective: This study modified the Revised Illness Perception Questionnaire (IPQ-R) in patients with persistent atrial fibrillation (AF). Design: Qualitative interviews and think-aloud techniques informed modification of the IPQ-R to be specific to AF patients. Confirmatory Factor Analysis (CFA) (n = 198) examined the validity of the modified IPQ-R (AF-IPQ-R). Exploratory factor analysis (EFA) examined the new AF-triggers scale. Construct validity examined associations between the AF-IPQ-R, quality of life (Qo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 62 publications
(62 reference statements)
5
17
0
Order By: Relevance
“…In line with the expectations based on Horne’s [ 27 ] assumption and previous results [ 47 , 52 , 53 , 54 , 55 , 56 , 57 ], all illness representation dimensions except for timeline were significantly related to perceptions of the necessity of COVID-19 vaccination. The pattern of the bivariate associations suggests that negative illness representations in terms of illness seriousness and emotional impact as well as positive illness representations in terms of treatment control and prevention control go together with the perception of a personal need for COVID-19 vaccination.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with the expectations based on Horne’s [ 27 ] assumption and previous results [ 47 , 52 , 53 , 54 , 55 , 56 , 57 ], all illness representation dimensions except for timeline were significantly related to perceptions of the necessity of COVID-19 vaccination. The pattern of the bivariate associations suggests that negative illness representations in terms of illness seriousness and emotional impact as well as positive illness representations in terms of treatment control and prevention control go together with the perception of a personal need for COVID-19 vaccination.…”
Section: Discussionsupporting
confidence: 90%
“…Empirical studies indeed showed that perceptions of severe symptoms, a long duration, and many adverse consequences stimulate perceptions of necessity. Additionally, it was found that stronger perceptions of the effectiveness of the pharmaceutical in controlling the illness or its onset, stronger emotional representations, and a better understanding of the illness are related to stronger necessity perceptions [ 47 , 52 , 53 , 54 , 55 , 56 , 57 ]. On the other hand, concerns about a specific pharmaceutical are not likely to be influenced by illness representations, but are rather informed by general beliefs about the nature of medicines or by past experiences with particular medicines than by illness representations [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A further important development of the IPQ-R inventory is the introduction of a measure of emotional representations, which captures individuals' beliefs that thinking about the illness is associated with negative emotions such as anger, anxiety, depression, and worry 1 . The questionnaire provides a sample of generic questions that might be employed to assess relevant dimensions, but also encourages researchers to modify these to specific disease-relevant content related to the identity, cause, timeline, consequences, coherence, and control dimensions derived from pilot work, extant literature, and medical knowledge (French & Weinman, 2008;Moss-Morris et al, 2002;Taylor et al, 2018;Weinman et al, 2018).…”
Section: Dimensions Of Illness Representationmentioning
confidence: 99%
“…The revised Illness Perception Questionnaire (IPQ-R) was developed by Moss-Morris et al in 2002 [11]. It includes 44 items and measures 7 subscales of the timeline (acute/chronic), timeline (cyclical), consequences, personal control, treatment control, illness coherence, and emotional representation.…”
Section: Illness Perception Questionnaire (Ipq)mentioning
confidence: 99%